UNCOVERING DECEPTIVE DISCOURSE IN IUU FISHING INVESTIGATIONS: A FORENSIC LINGUISTIC STUDY - M. Natsir Amir; Ifan Iskandar; Yasir Riady; Nuryansyah Adijaya (Indonesian EFL Journal, 2026)
This study pioneers the application of forensic linguistics to investigative interviews in Illegal, Unreported, and Unregulated (IUU) fishing enforcement. It aims to identify and systematize the specific linguistic and discursive strategies used by suspects to construct deceptive narratives, thereby developing an evidence-based analytical framework for this underexplored domain of environmental crime. Employing a qualitative case study design within an interpretivist paradigm, the research analyses a corpus of 15 authentic, anonymized investigative interview transcripts from concluded IUU fishing cases in Indonesia. Data were analyzed using a multi-stage forensic linguistic protocol, combining deductive coding informed by established deception markers (e.g., hedging, narrative inconsistency, pragmatic deflection) with inductive thematic analysis to identify context-specific strategies. Analytical rigor was ensured through analyst triangulation and thick description. The analysis reveals a consistent “Four-Pillar” model of deceptive discourse in IUU investigations: 1) Lexical-Pragmatic Evasion (e.g., pervasive hedging, passive constructions, deictic distancing); 2) Narrative Manipulation (e.g., chronological inconsistencies, lack of sensory detail for illicit acts, overly rehearsed formulae); 3) Pragmatic-Discursive Deflection (e.g., failure to answer questions directly, attribution of agency to external forces, appeals to norms); and 4) Socio-Linguistic Masking (e.g., strategic use/omission of technical jargon, feigned linguistic misunderstanding). These interconnected strategies function to obfuscate truth, diffuse responsibility, and exploit the technical and multilingual context of fisheries operations. This study is the first to conduct a dedicated forensic linguistic examination of deception within IUU fishing investigations. It moves beyond generic deception detection models by constructing a context-specific framework that accounts for the unique technical, legal, and operational realities of maritime environmental crime. The research provides both a theoretical contribution to forensic linguistics and a practical, actionable toolkit for enhancing the investigative and prosecutorial processes in fisheries law enforcement.